2021
DOI: 10.3390/genes12091373
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Tumor Propagating Cells in Fusion-Positive Rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma in children. Fusion-positive RMS (FPRMS), expressing the PAX3/7-FOXO1, has a worse prognosis compared to the more common fusion-negative RMS (FNRMS). Although several studies reported hierarchical organization for FNRMS with the identification of cancer stem cells, the cellular organization of FPRMS is not yet clear. In this study we investigated the expression of key stem cell markers, developed a sphere assay, and investigated the seven most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
2
1
0
Order By: Relevance
“…However, the authors did not detect a reversed switch from the differentiated state to mesenchymal-like state in eRMS ( 49 ), which could be a unique characteristic of the aggressive aRMS subtype. Our results are in line with a previous report that failed to detect a cancer stem cell (CSC) subpopulation with self-renewing and tumor-initiating properties in aRMS ( 51 ), rather suggesting a role for cellular plasticity instead of the classical CSC hypothesis at the root of this tumor resistance and aggressiveness.…”
Section: Discussionsupporting
confidence: 92%
“…However, the authors did not detect a reversed switch from the differentiated state to mesenchymal-like state in eRMS ( 49 ), which could be a unique characteristic of the aggressive aRMS subtype. Our results are in line with a previous report that failed to detect a cancer stem cell (CSC) subpopulation with self-renewing and tumor-initiating properties in aRMS ( 51 ), rather suggesting a role for cellular plasticity instead of the classical CSC hypothesis at the root of this tumor resistance and aggressiveness.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies using fluorescent transgenic zebrafish bearing KRAS(G12D)induced RMS yielded similar insights [100]: GFP-labeled MYF5 high zebrafish tumor cells (expressing markers of satellite and early muscle progenitor cells) and mCherry-labeled MYF4 high zebrafish tumor cells (expressing high levels of mature muscle markers) were By contrast, PF+ RMS displays more prominent intrinsic plasticity, with both stem-like and cycling-myoblast states having the capacity to re-create the original composition of the tumor. These observations are consistent with in vivo tumor-propagating capacity of all single-cell clone-derived clones of P3F+ RMS cells examined by Generali et al [101]. Of note, fluctuating levels of P3F expression in single, mouse P3F+ RMS cells were linked to differences in in vitro clonal activity and in vivo tumor-propagating capacity, indicating plasticity in P3F expression at the single-cell level [91].…”
Section: Cellular Hierarchies In Rmssupporting
confidence: 89%
“…Our work also suggests that FP-RMS may not follow the rigid-stem cell hierarchies found in development. In fact, limiting dilution cell transplantation assays using engraftment into immune deficient mice have shown that FP-RMS have a high frequency for tumor initiation [49], raising the possibility that most if not all FP-RMS cells can acquire the ability to propagate tumors in vivo . Such a model would be consistent with reports where drug-induced neuroendocrine transdifferentiation serves as an escape mechanism for melanoma and castration-resistant prostate cancer [50, 51].…”
Section: Discussionmentioning
confidence: 99%